Complementary methodologies’ evaluation of endodontically treated teeth restored with precast posts. A literature review - dos Santos Neto, Otavio Marino (2021)
The restoration of endodontically treated teeth (RETT) is a subject in constant study, in order to obtain safe clinical protocols that can improve treatments longevity. In recent years, the search for complementary methodologies to bond-strength proves has been growing for evaluating RETTE, being important to know the most used complementary methods’ advantages and disadvantages to evaluate this. The aim of this study is to present a literature review on complementary methods to bond strength and the fracture strength tests. The articles search was done in databases: PUBMED, BBO (Brazilian Dental Library), LILACS (Health Literature of Latin America and the Caribbean), SciELO and Medline, using the keywords “endodontically treated teeth” and “prefabricated post” from 1990 to 2020. Out of 360 articles 295 were excluded because they did not present relevant information for this research, since the methodologies included microbiological, molecular, biological tests, imaging methodologies, and surface analysis methods. The techniques used in each selected article were listed, and starting from them, a new bibliographic search was carried out, with the aim of reviewing the techniques and their potential uses, advantages and disadvantages. It was concluded that the presented techniques were valuable to increase the obtained results with the mechanical proves in RETT evaluation with prefabricated posts.